The formation of a metallosupramolecular porous helicate through salicylaldehydethiosemicarbazone: Synthesis, Characterization, Cytotoxic activity, DNA binding and DFT calculations - Altiparmak, Elif Avcu; Eroglu, Gunes Ozen; Ozcelik, Elif; Ozdemir, Narvik; Kuruca, Serap Erdem; Arsu, Nergis; Ulkuseven, Bahri; Bal-Demirci, Tulay (WILEY, 2019)
The reaction of salicylaldehyde-S-methylisothiosemicarbazone in the presence of ethylenediamine base and iron (III)chloride generated unforeseen homotopic dinuclear triple-stranded iron (III)helicate. The synthesized helicate was characterized by elemental analysis, IR, UV-Vis spectroscopy, magnetic moment measurement, and evaluated cytotoxic activities against K562, HL-60 and THP-1 leukemia cells. In addition, solid-state structure has been determined by single-crystal X-ray diffraction technique. In the complex, three dinucleating O, N, N, O donor ligands provide three diazine (NN) bridges between the metal ions and facial O3N3 coordination spheres around them. The ligands are folded about the NN single bond and coordinated to the two metal ions in a helical fashion to form the triple helical structure. In the crystal lattice, chains of centrosymmetric R22 >12 rings, which are connected to one another via pi pi stacking interactions, are generated by CH center dot center dot center dot O intermolecular interactions. The results are also confirmed by the density functional theory (DFT) calculations. The results obtained from the cytotoxicity test showed to be effective in low concentrations on the leukemia cells. An intercalative binding mode of helicate-DNA complex was confirmed with the high intrinsic binding constant (K-b = 8x10(6) M-1) and competitive displacement assay of Ethidium bromide with high Ksv value.
Keywords: cytotoxicity; DFT; DNA binding; Helicate; supramolecular; MOLECULAR-ORBITAL METHODS; MIXED-LIGAND COMPLEXES; CRYSTAL-STRUCTURE; BASIS-SET; IRON; THIOSEMICARBAZONES; METALLOHELICES; INTERCALATORS; RECOGNITION; IRON(III); Chemistry